The Influence of Competence and Work Environment on the Work Spirit of BPBD Members of Tasikmalaya City - Shofi Noer Fadillah; Cece Rakhmat; Arga Sutrisna (Journal of Indonesian Management, 2022)
This study aims to determine the effect of Competence and Work Environment on the morale of BPBD members in Tasikmalaya City. In this study, the three variables used an ordinal measuring scale. The method used is descriptive verification with a quantitative approach. The sampling technique used is based on the purposive sampling technique. The object of this research is the work spirit of the BPBD Tasikmalaya City (BPBD task force) members, totaling 32 people. The analytical tool used is multiple linear regression. The results of this study indicate that Competence and Work Environment simultaneously have a significant effect, competence partially has a significant effect and the work environment partially has no significant effect on the Work Spirit of BPBD Members in Tasikmalaya City.